The Protective Roles of Urinary Trypsin Inhibitor in Brain Injury Following Fat Embolism Syndrome in a Rat Model. Issue 6 (June 2019) - Xiong, Lili; Sun, Linlin; Liu, Shanshan; Zhu, Xingyun; Teng, Ze; Yan, Junhao
Fat embolism syndrome (FES) is a common complication following long bone fracture; fat droplets are released into the blood circulation and form embolisms, mainly in lung and brain. However, the potential mechanisms involved remain to be clarified. In this study, the mechanism of brain injury following FES and the protective effects of urinary trypsin inhibitor (UTI)—a serine protease inhibitor—were investigated. Sixty male Sprague-Dawley rats were divided randomly into sham, FES and FES+UTI treatment groups. The FES model was established using tail vein injection of glycerol trioleate, and UTI was administered by intraperitoneal injection immediately following FES. Brain/lung water content evaluation, Evans blue content and magnetic resonance imaging examination were used to assess the effects of UTI. Furthermore, immunohistochemistry and western blot were also applied to explore the protective mechanism of UTI following FES. The results of oil red O staining indicated that the FES model was successfully established. UTI could significantly attenuate blood-brain-barrier (BBB) disruption, as seen through brain edema evaluation and Evans blue content examination. Immunofluorescence staining results indicated that the TLR4-JNK pathway was involved in brain injury after FES; this effect could be quenched by UTI treatment. Furthermore, UTI could decrease the levels of downstream target proteins of the TLR4-JNK pathway, phosphorylated-NF- κB (p65) and p53 in brain. Our results showed that UTI could alleviate BBB injury after FES through blocking activity of the TLR4-JNK pathway.